Emotions in Music and their Impact on the Emotions of Percipients: Research on Human Voice and Singing - Sláviková Zuzana; Králová Eva (Sciendo, 2021)
The field of psychology of singing is the least examined area so far, so in the research study we present the research survey from the field of human voice and singing. Music allows the access to the experience of emotions, which can then manifest itself in various changes at a psychosomatic level. New research findings can therefore be used very effectively in the field of music therapy or singing. The anthropological idea of this phenomenon is based on the fact that the human voice is an extremely sensitive physical and emotional tool through which it is possible to act on the body, psyche and spirit, in terms of complex personality development and to discover human contact with its deeper, archetypal components. The sound experience of singing can touch a person's most basic existential experiences. In this study we want to reveal the underappreciated possibilities of using the human voice and singing in the field of music therapy and point out the purposeful development of vocal dispositions, in concord with the core of human personality (conscious and unconscious). Mainly owing to strong emotions, it has a significant impact on harmonisation of hemispheres, stimulation of all mental functions that leads to spontaneous revitalisation of the psyche and body and it subsequently leads to improved quality of life.